Letter to Jane Tolmach from M. Kathleen Belton, M.D. - M. Kathleen Belton:::::: (1976)
In a June 9, 1976 letter, Dr. M. Kathleen Belton congratulates Jane Tolmach on winning the Democratic nomination for State Assembly and confirms her support. She encloses a campaign contribution and offers to assist Tolmach's campaign in any way her medical practice will allow. Dr. Belton emphasizes that her support is based not on feminist ideology, but on her belief in Tolmach's proven effectiveness as a local legislator and her attentiveness to community needs. She offers permission to use her name publicly in campaign materials and volunteers to help with speeches and gathering support. The letter closes with warm encouragement and best wishes for Tolmach's success in the campaign.